Clinical Implementation and Evaluation of Three Implementation Interventions for a Family-Oriented Care for Children of Mentally Ill Parents (ci-chimps): Study Protocol for a Randomized Controlled Multicenter Trial - Laser, Carolin; Modarressi, Anna; Skogøy, Bjørg Eva; Reupert, Andrea; Daubmann, Anne; Höller, Alexandra; Zapf, Antonia; Pawils, Silke; Taubner, Svenja; Winter, Sibylle; Maybery, Darryl; Wiegand-Grefe, Silke (Frontiers in Psychiatry, 2022)
In Germany, approximately three million children under the age of eighteen have a mentally ill parent. These children are at an increased risk of developing a mental illness themselves (1) as well as a physical illness (2). While research has identified numerous evidence-based family-oriented interventions, little is known about how to implement such interventions effectively and efficiently in clinical practice in Germany. This implementation study (ci-CHIMPS) evaluates three clinical implementation projects with three different implementation interventions for the optimal implementation of the tailored family-oriented preventive and therapeutic interventions in the CHIMPS-NET (children of mentally ill parents – research network) with an implementation model for children of mentally ill parents. Methods: A two-group randomized controlled multicenter trial will examine changes in family-oriented practice and aspects of implementation at baseline as well as at 12- and 24-months follow-up. The CHIMPS-Network consists of twenty clinical centers. The centers in the intervention group receive the support of all of the three implementation interventions: 1) optimal pathways to care, 2) education and a training program for professionals and 3) systematic screening for children. The centers in the control group do not get this specific implementation support. Discussion: While we know that children of mentally ill parents are an important target group to be addressed by preventive and therapeutic interventions, there is often a lack of structured implementation of family-oriented interventions in clinical practice in Germany. Using a randomized controlled multicenter trial design with a large and wide-ranging sample (clinics for adult psychiatry and clinics for child and adolescent psychiatry, university clinics and clinics at the real health care) will provide a robust understanding of implementing family-oriented changes in German clinical practice.